Creation interpretation which reflects ancient time - Tursunaliyeva Ruzigul Xolmurzayevna.; A’zamjon Abduhalilov (Genius Journals, 2022)
The article discusses the philosophical aspects of the performance "Bakhrom and Dilorom" based on the work of our great writer Alisher Navoi Sabbayi Sayyar, the interaction of puppets and actors. Analytical judgments are given about how brightly the inner world and skill of each actor are reflected in the image he portrays.
Keywords: Art; theatre; culture; youth